Therapeutic approaches for liver fibrosis/cirrhosis by targeting pyroptosis - Qiao Guanen; Li Pan; Wang Meng; Li Changjuan; Wang Yanmei; Xin Shuanli; Liu Haitao (Open Life Sciences, 2025)
Long-term repeated exposure to various stimuli leads to chronic liver damage, inflammation, fibrosis, and eventually cirrhosis. Pyroptosis, a mode of inflammatory programed cell death, affects the progression of liver fibrosis/cirrhosis. However, current research on drugs targeting the pyroptosis pathway as a therapeutic strategy in liver fibrosis and cirrhosis remains limited. This review aims to explain the relationship between pyroptosis and liver cirrhosis and focuses on methods for the treatment of liver cirrhosis based on targeted pyroptosis. Here, 31 inhibitor drugs that target inflammasomes, gasdermin D, or caspases are discussed. Although the inhibitory effect of these drugs on pyroptosis is indisputable, their efficacy on cirrhosis needs a thorough investigation. Seventeen natural plant compounds that improve liver fibrosis/cirrhosis in cellular and animal models through targeting pyroptosis are also reviewed. In addition, stem cell replacement therapy and exosomes have broad application prospects in liver cirrhosis from the perspective of pyroptosis. In the future, the primary challenges will involve validating the efficacy of the aforementioned drugs in targeting pyroptosis for cirrhosis treatment using human liver organoids as well as determining their potential clinical application.